Prevalence of toxin genes among the clinical isolates of Staphylococcus aureus and its clinical impact - Divya Deodhar (Journal of Global Infectious Diseases, 2015)
Introduction: Staphylococcus aureus (S. aureus) causes a variety of infections, ranging from a mild skin infection to blood stream infections and deep seated infections. As Stapylococcus aureus bacteremia (SAB) has the tendency to cause endovascular and metastatic infections, complications can occur at almost all sites of the body. Hence, SAB is associated with increased morbidity and mortality in spite of appropriate antimicrobial treatment. The virulence in S. aureus is determined by the presence of adhesins and toxins, which behave like superantigens (SAgs) and leads to a massive release of proinflammatory cytokines causing overwhelming inflammatory response leading to endothelial leakage, hemodynamic shock, multiorgan failure, and possibly death. Materials and Methods: One year prospective study conducted in a tertiary care hospital in southern part of India included all patients with SAB. Clinical details were filled according to. All isolates were subjected to polymerase chain reaction (PCR) for enterotoxin profiling. Results: A total of 101 patients of SAB were identified which comprises of 61 (60.4%) patients with methicillin-susceptible S. aureus (MSSA) and 40 (39.6%) patients with methicillin-resistant S. aureus (MRSA). Most common predictors of mortality were prior hospitalization and antibiotic intake, severe organ dysfunction, shock, tachycardia, and leukocytosis. Two-third of the isolates had at least one enterotoxin, most prevalent was sea; 28% and 27% (P - value = 0.001) MSSA isolates had seg and sei; whereas, 38.6% (P - value < 0.001) of MRSA isolates were found to have sea. The most common enterotoxin associated with mortality was sei, which comprised of 38% of all mortality. Conclusion: In SAB, the significant predictors of mortality were prior hospitalization and antibiotic intake, presence of multiorgan dysfunction, and shock. Although overall significance between the enterotoxin and shock could not be demonstrated, it successfully demonstrated the difference of enterotoxin between MSSA and MRSA.